The Effectiveness of Tornado Physics Enrichment Book to Increase Science Literacy of High School Students - Nurul Izzah; Desnita Desnita (Jurnal Penelitian Pendidikan IPA, 2023)
Scientific literacy is a need and learning goal in the industrial era 4.0. Indonesia's low scientific literacy is an urgent problem. There are many ways that can be used in learning to hone scientific literacy, including choosing sources and teaching materials that are integrated with natural disaster environmental. In this research, scientific literacy was sharpened in physics learning through the use of a knowledge enrichment book entitled Tornado. In this enrichment book, the discussion of tornadoes is presented from a physics perspective including the concepts of energy, heat, fluid dynamics and global warming. The aim of this research is to increase students' scientific literacy by using physics enrichment books on the theme of the tornado disaster. This research uses an experimental research method in the form of a quasi-experimental design with a one-group pretest-posttest design. The results of the trial of 60 students from SMAN 13 Padang and SMAN 2 Padang Panjang showed that the use of enrichment books was able to increase students' scientific literacy, with an average pretest scientific literacy of 46 and an average posttest of 87, and an N-gain of 0.76. These results indicate that the use of tornado physics enrichment books is effective in increasing students' scientific literacy.